Chromosomal lesions and uniparental disomy detected by SNP arrays in MDS, MDS/MPD, and MDS-derived AML - Gondek, Lukasz P. (American Society of Hematology, 2008)
Using metaphase cytogenetics (MC), chromosomal abnormalities are found in only a proportion of patients with myelodysplastic syndrome (MDS). We hypothesized that with new precise methods more cryptic karyotypic lesions can be uncovered that may show important clinical implications. We have applied 250K single nucleotide polymorphisms (SNP) arrays (SNP-A) to study chromosomal lesions in samples from 174 patients (94 MDS, 33 secondary acute myeloid leukemia [sAML], and 47 myelodysplastic/myeloproliferative disease [MDS/MPD]) and 76 controls. Using SNP-A, aberrations were found in around three-fourths of MDS, MDS/MPD, and sAML (vs 59%, 37%, 53% by MC; in 8% of patients MC was unsuccessful). Previously unrecognized lesions were detected in patients with normal MC and in those with known lesions. Moreover, segmental uniparental disomy (UPD) was found in 20% of MDS, 23% of sAML, and 35% of MDS/MPD patients, a lesion resulting in copy-neutral loss of heterozygosity undetectable by MC. The potential clinical significance of abnormalities detected by SNP-A, but not seen on MC, was demonstrated by their impact on overall survival. UPD involving chromosomes frequently affected by deletions may have prognostic implications similar to the deletions visible by MC. SNP-A–based karyotyping shows superior resolution for chromosomal defects, including UPD. This technique further complements MC to improve clinical prognosis and targeted therapies.